2015
DOI: 10.1188/15.cjon.19-01ap
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Changes Associated With Cancer and Cancer Treatment: State of the Science

Abstract: Evidence-based interventions to address cognitive changes after cancer and cancer treatment are limited. However, emerging research has demonstrated that nonpharmacologic treatments, such as cognitive training, are likely to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…There is accumulating evidence documenting cognitive impairment issues among cancer survivors, but this is mainly dominated by breast cancer survivors. 22 The prevalence of cognitive complaints among Chinese cervical cancer survivors was 64.5%, which is consistent with previous research. 6 As this study was preliminary and adopted a small and non-random sample, epidemiological studies are needed to further quantify the prevalence, impact and extent of cognitive complaints in this study population.…”
Section: Discussionsupporting
confidence: 91%
“…There is accumulating evidence documenting cognitive impairment issues among cancer survivors, but this is mainly dominated by breast cancer survivors. 22 The prevalence of cognitive complaints among Chinese cervical cancer survivors was 64.5%, which is consistent with previous research. 6 As this study was preliminary and adopted a small and non-random sample, epidemiological studies are needed to further quantify the prevalence, impact and extent of cognitive complaints in this study population.…”
Section: Discussionsupporting
confidence: 91%
“…Thus repeated acute stress may be associated with decreased working and recognition memory. An additional study has suggested that cognitive impairment may be due to neurotoxic or microvascular injuries, inflammation, regulatory issues with the hypothalamic-pituitary-adrenal axis that could impact brain hormone concentrations, or increases in the rate of cellular aging, as a result of cancer tumor or treatment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 49 Another interesting aspect is that cancer and cancer treatment on its own can lead to cognitive impairment, which highlights the need for more knowledge and guidelines about the particularities of this group and how it should be treated. 50 …”
Section: Discussionmentioning
confidence: 99%